Dexmedetomidine versus esmolol to attenuate the hemodynamic response to laryngoscopy and tracheal intubation: A randomized double-blind clinical study - Reddy, Siddareddigari Velayudha (Medknow Publications & Media Pvt Ltd, 2014)
CONTEXT: Sympathoadrenal response to laryngoscopy and tracheal intubation manifests as transient, but distinct tachycardia and hypertension. AIMS: The objective of this study is to compare the clinical effects of dexmedetomidine with esmolol and control in attenuating the presser response during laryngoscopy. SETTINGS AND DESIGN: A randomized, prospective, double-blind, controlled study. SUBJECTS AND METHODS: We studied consented, 90 adult, American Society of Anesthesiologists physical status I and II patients of either sex, scheduled for non-cardiac surgery requiring intubation. The patients were randomly divided into three groups (n = 30). Group C received placebo, Group E received 2.0 mg/kg of esmolol and Group D received 1.0 μg/kg of dexmedetomidine, intravenously over 10 min and 3 min before induction of general anesthesia. All patients were uniformly pre-medicated, induced and intubated using thiopentone and succinylcholine as per standard protocol. Heart rate (HR), systemic arterial pressures were recorded at baseline, after study drug infusion, after induction, immediately and 3, 5, 7, 10 min after intubation. STATISTICAL ANALYSIS: Analysis of variance and t-test as appropriate. RESULTS: The mean arterial pressure was significantly increased in patients receiving placebo (P < 0.0001) and esmolol (P < 0.0001) after laryngoscopy and intubation compared with baseline value and Group D (P = 0.6294). The rise in HR (P = 0.08481) and rate pressure product (P = 0.0666) at the time of intubation were minimal and was statistically significant up to 15 min in Group D. CONCLUSIONS: Both the drugs attenuated the pressure response. Of the two drugs administered, dexmedetomidine 1.0 μg/kg provides a consistent, reliable and effective attenuation of pressure responses when compared to esmolol 2.0 mg/kg.